Uncertain fault diagnosis problem using neuro-fuzzy approach and probabilistic model for manufacturing systems, ISSN / e-ISSN 0924-669X / 1573-7497 - Djelloul Imene; Sari Zaki; Latreche Khaled (Applied Intelligence volume, 2018)
This paper is concerned with fault detection and diagnosis problem in manufacturing systems. In such industrial environment, production systems are subject to several faults caused by a number of factors including the environment, the accumulated wearing, usage, etc. However, due to the lack of accuracy or fluctuation of data, it is oftentimes impossible to evaluate precisely the correct classification rate of faults. In order to classify each type of fault, neural networks and fuzzy logic are two different intelligent diagnosis methods that are more applied now, and each has its own advantages and disadvantages. A new hybrid fault diagnosis approach is introduced in this paper that considers the combined learning algorithm and knowledge base (Fuzzy rules) to handle ambiguous and even erroneous information. Therefore, to enhance the classification accuracy, three perceptron models including: linear perceptron (LP), multilayer perceptron (MLP) and fuzzy perceptron (FP) have been respectively established and compared. The conditional risk function “PDF” that measures the expectation of loss when taking an action is presented at the same time. We evaluate the proposed hybrid approach “Variable Learning Rate Gradient Descent with Bayes’ Maximum Likelihood formula” VLRGD-BML on dataset of milk pasteurization process and compare our approach with other similar published works for fault diagnosis in the literature. Comparative results indicate the higher efficiency and effectiveness of the proposed approach with fuzzy perceptron for uncertain fault diagnosis problem.